Unraveling the role of gravity in shaping intruder dynamics within vibrated granular media - Ke Cheng; Meiying Hou; Wei Sun; Zhihong Qiao; Xiang Li; Chufan Lai; Jinchao Yuan; Tuo Li; Fangfu Ye; Ke Chen; Mingcheng Yang (Communications Physics)
Abstract Our experiments aboard the Chinese Space Station reveal a gravity-driven transition in intruder dynamics within vibrated granular media. While vibrations typically enable an intruder to ascend in a granular bed, low-gravity conditions induce it to descend under similar vibrations. Using a Hall-sensor array tracking method, we monitor the intruder’s movement throughout each vibration cycle and identified two competing mechanisms: inertia and gravity-dependent penetration. As gravity decreases, we observe a significant reduction in the scaled damping coefficient and hydrostatic pressure coefficient indicating that bed particles disperse more readily upon intruder impact, facilitating deeper penetration. Our findings highlight a critical transition from downward to upward motion of the intruder as vibration acceleration exceeds a threshold, which increases as gravity decreases. These insights into intruder dynamics in low-gravity environments have significant implications for asteroid exploration and lunar base construction, enhancing our understanding of the Brazil nut effect and the formation of planetesimal.